The association between subjective wellness symptoms and blood biomarker data in English Premier League footballers - Cleary, M.; McHugh, F.; Paradis, K. F. (Journal of Science in Sport and Exercise, 2023)
The present study investigates the association between subjective wellness symptoms, and categorical point-of-care (POC) blood biomarkers of the free oxygen radical test (FORT), and systemic inflammation through high sensitivity C-reactive protein (Hs-CRP), in English Premier League footballers. Data from 38 male professional elite athletes (Mean Age = 25.8, SD = 4.4) from the English Premier League were included in the study, with a total of 674 individual testing records collected over an entire Premier League season. A player wellness questionnaire, along with fasted and rested point-of-care blood biomarker testing were collected weekly across the season. The wellness questionnaire collected subjective symptoms of illness and fatigue, while FORT and Hs-CRP were assessed through point-of-care analysis to highlight periods of excessive hydroperoxide production and systemic inflammation. Using a chi square goodness of fit model, results showed that there was a significant association between the frequency of symptoms logged and categorical POC blood biomarker data of FORT and HsCRP (P < 0.01). Of the records demonstrating normal levels of Hs-CRP and FORT concentrations, 27% logged symptoms with an average of 1.5 symptoms reported per answered record. Comparatively, excessive biomarker values demonstrated 55% of records having symptoms logged, averaging 2.4 symptoms reported per record.